Epidemiological Situation on COVID-19 in Irkutsk Region and Forecast for its Spread - S. V. Balakhonov; M. V. Chesnokova; A. N. Perezhogin; A. Ya. Nikitin; S. V. Kaverzina; N. V. Breneva; Z. F. Dugarzhapova; D. F. Savinykh; N. E. Potalitsina; T. A. Gavrilova; N. A. Likhanova; I. G. Chumachenko; et al. (Проблемы особо опасных инфекций, 2021)
Assessment of a particular territory by its epidemiological significance is very relevant in the light of widespread occurrence of new coronavirus infection, COVID-19, in the Russian Federation.Objective. Detection of the epidemiological features and revealing trends in the epidemic process of new coronavirus infection in the Irkutsk Region and forecasting of its spread.Materials and methods. An operational analysis of the epidemiological situation on COVID-19 in the Irkutsk Region as of August 16, 2020 was performed. Restrictive measures were substantiated based on the calculation of the infection spread rate (Rt).Results and discussion. Irkutsk Region remained one of the adverse territories as regards human COVID-19 incidence in the Siberian Federal District and the Russian Federation as of August 16, 2020. The gradual dynamics of the epidemic process was revealed: at the first stage of the epidemic development it was facilitated by the imported cases from affected countries and regions of the Russian Federation, and subsequently by local transmission. The incidence increase was registered 2 months later than in central regions of the Russian Federation. Currently there is a consistent downward trend. The increase in the cases prevailed among rotation workers staying for shift and seasonal activities in the administrative center and northern districts of the Irkutsk Region. The epidemic pattern was determined by gender, age and social characteristics. It is demonstrated that the risk of the new coronavirus infection is determined by the intensity of contacts in family foci, the spread of infection in medical organizations and a significant proportion of asymptomatic carriers. High lethality rates (0.7 %) and mortality rates (31.1 o / oooo) were established among persons over 65 years. The stationary time series observed since June for changing the Rt-indicator with fluctuations ranging from 0.92 to 1.01 requires maintaining control of restrictive measures with prompt management decisions making based on the evolving epidemiological situation in the Irkutsk Region and taking into account the assessment of its possible complication risks.